Composite protective coating for metal surface and preparation method thereof
By using a composite protective coating composed of a silicon-based ceramic precursor and a terpent-containing filler phase, a three-dimensional mesh-gap structure and sintering modification technology, the problem of the existing coating lacking protection ability in high-temperature environments is solved, and an efficient and environmentally friendly protective effect is achieved.
Patent Information
- Application Number
- CN202411568643.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing protective coatings lack protection capabilities in high temperature environments, and there are high energy consumption and pollution problems in the production process.
The composite protective coating consisting of a preceramic phase formed by a silicon-based ceramic precursor and an aluminum-containing filler phase is used to improve the oxidation and corrosion resistance of the coating through a three-dimensional mesh-gap structure and sintering modification technology.
It has achieved effective protection in a high temperature environment of 300~1100℃, reduced production energy consumption and pollution, and significantly improved coating hardness.
Smart Images

Figure CN119592222A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of protective coatings, in particular to a composite protective coating for metal surfaces and a preparation method thereof. Background Art
[0002] During production or service, metal workpieces / parts often suffer from surface quality deterioration such as oxidation and corrosion. To solve this problem, coating protection methods are often used to improve the surface quality of metal workpieces / parts and enhance their oxidation resistance and corrosion resistance. According to the type of coating material, commonly used protective coatings include: metal coatings, polymer coatings, ceramic coatings, etc.; according to the production method, commonly used protective coatings include: electroplating coatings, hot-dip coatings, vacuum zinc (aluminum) coatings, thermal sintering coatings, spray paint coatings, etc.
[0003] Aluminum is the most abundant metal element in the earth's crust. It has excellent ductility and can be easily processed into various forms such as sheets, foils, powders, and rods. Because it can form an oxide film in the air to prevent metal corrosion, aluminum has excellent protective properties. Based on this feature, aluminum is widely used in the field of protective coatings.
[0004] Zinc-aluminum coating is a thermally sintered coating that has corrosion resistance, no hydrogen embrittlement, heat resistance, and recoatability. Prior art CN202111530080 and CN202211261479 disclose a zinc-aluminum coating that removes hexavalent chromium ions; prior art CN202211597473 discloses a nano zinc-aluminum polymer coating with protective properties; prior art CN201611019186 discloses a high-temperature resistant zinc-aluminum coating that improves the high-temperature corrosion resistance and thermal shock resistance of the coating. However, the heat resistance of these coatings is only below 400°C, and the coatings do not have the ability to protect the substrate from oxidation at higher temperatures.
[0005] Aluminum-silicon coatings, zinc-based coatings, and zinc-aluminum-magnesium coatings are currently commonly used hot-dip coatings. They have excellent oxidation resistance, corrosion resistance, and economy, and have been widely used in industry. Aluminum-silicon coatings have excellent oxidation resistance at high temperatures, and their coating plates are widely used in hot stamping. For example, in the prior art CN201910840478 and CN200980103702, aluminum-silicon coating plates were developed for the production of high-strength workpieces. The oxidation resistance of zinc-based coatings is slightly worse than that of aluminum-silicon coatings, and it is easy to cause liquid metal brittle fracture of the metal matrix at high temperatures, so it is rarely used for high-temperature protection. Zinc-aluminum-magnesium coatings have excellent protective effects at room temperature, but they are also rarely used for high-temperature protection. Since the coating raw materials need to be heated to a higher temperature and kept warm for a long time during hot-dip production, these protective coatings are often accompanied by higher energy consumption during production. In addition, the production of electroplating coating and vacuum zinc (aluminum) coating is accompanied by serious pollution problems, such as: electroplating coating production produces wastewater pollution, vacuum zinc (aluminum) coating production cycle is long, easy to produce dust leading to air pollution. Spray paint coating can only be used for room temperature corrosion protection.
[0006] Polymer coating is also a commonly used protective coating, which can provide protection for workpieces, such as the polymer coating provided by the prior art CN202311590015 and CN202410285566. This coating processing technology is usually simple and easy to prepare. However, at present, polymer coatings are usually only suitable for room temperature or lower temperature environments and do not have high temperature protection capabilities. Ceramic coatings usually have high temperature protection capabilities, but the materials they protect are usually non-metallic materials (such as prior art: CN202311840206, CN202311601832).
[0007] In summary, there is a need to develop a composite coating material that has the advantages of the above-mentioned coatings, which has the following features: simple production process, high and low temperature oxidation resistance, corrosion resistance, can be used on metal substrates, pollution-free production process and low energy consumption. Summary of the invention
[0008] The present invention is made in view of the deficiencies in the prior art, and aims to provide a composite protective coating for metal surfaces and a preparation method thereof.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] The present invention provides a composite protective coating for metal surfaces, wherein the coating consists of a preceramic phase formed by a silicon-based ceramic precursor and an aluminum-containing filler phase, wherein the preceramic phase is connected to form a three-dimensional network structure in the coating, and the filler phase is distributed in the gaps of the preceramic phase, and the coating presents a three-dimensional network-gap structure; wherein the volume fraction of the preceramic phase is ≤80%, and the volume fraction of the filler phase is ≥20%.
[0011] Furthermore, the volume fraction of the pre-ceramic phase is 10-80%, and the volume fraction of the filler phase is 20-90%.
[0012] Furthermore, after the coating is prepared, the coating can be kept warm for 0.5 to 30 minutes in an environment of 300 to 1100°C for sintering modification; after the coating is sintered and modified, part or all of the structure of the coating is transformed, that is, the pre-ceramic phase and the filler phase in the coating will each react differently according to the sintering temperature and the sintering atmosphere. If the melting point of the filler is lower than 800°C, the pre-ceramic phase and the filler phase will also react. The reaction in the above process is at least one of the reaction of the pre-ceramic phase, the reaction of the filler phase, and the reaction between the pre-ceramic phase and the filler phase, generating a ceramic structure with a polycrystalline state, and the hardness of the coating is significantly improved.
[0013] The raw materials of the coating, i.e. the coating slurry, can be divided into two parts: the main material and the auxiliary material; the main material is the key component of the coating slurry, which is composed of a silicon-based ceramic precursor and a filler. The mass ratio of the ceramic precursor to the filler is 1:1~10:1; the auxiliary material is an auxiliary component of the coating slurry, which is composed of an auxiliary solvent and an auxiliary curing agent, and the auxiliary material can be selectively added or not; taking the mass fraction of the coating slurry as 100%, the main material accounts for 40~100% of the coating slurry, the auxiliary solvent in the auxiliary material accounts for 0~60% of the coating slurry, and the auxiliary curing agent in the auxiliary material accounts for 0~20% of the coating slurry, and the sum of the mass percentages of the above components is 100%; preferably, in the coating slurry, the main material accounts for 40~95% of the coating slurry, the auxiliary solvent in the auxiliary material accounts for 5~60% of the coating slurry, and the auxiliary curing agent in the auxiliary material accounts for 0~20% of the coating slurry, and the sum of the mass percentages of the above components is 100%.
[0014] Among the raw material components of the coating, the silicon-based ceramic precursor refers to an organic polymer material containing silicon in the main chain and / or side chain, which can be partially or completely converted into an inorganic ceramic phase after high-temperature pyrolysis, and is selected from at least one of polysilazane, polysiloxane, polycarbosilane, and polysilane, or an organic polymer modified with functional groups on the basis of the above organic polymers;
[0015] Preferably, in the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥70%. Since polysilazane usually has excellent antioxidant and corrosion resistance below 1200°C, in order for the coating to obtain excellent protective effects, the content of polysilazane in the silicon-based ceramic precursor must meet the above conditions. However, after sintering at above 300°C, polysiloxane, polycarbosilane, polysilane, etc., usually cannot protect the substrate from oxidation and corrosion, but their products can fill the gaps caused by sintering in the coating caused by polysilazane and improve the coating performance. Therefore, it is preferred to increase the content of polysilazane in the silicon-based ceramic precursor, and add a small amount of other types of silicon-based ceramic precursors.
[0016] Among the raw material components of the coating, the filler is composed of aluminum powder and other powders, and its composition by mass percentage is: 70-100% aluminum powder, 0-30% other powders, and the sum of the mass percentages of the above components is 100%. The aluminum powder is a powder of pure aluminum or aluminum alloy, and the aluminum alloy is preferably an alloy type with an aluminum mass fraction of ≥90%. The other powders are single powders of zinc, magnesium, titanium, and silicon, alloy powders of two or more elements of zinc, magnesium, titanium, and silicon, or compound powders containing aluminum, zinc, magnesium, titanium, and silicon; the microscopic shape of the filler is one or both of lamellar and granular, and the size range of the lamellar filler is preferably an equivalent diameter ≤70μm, and the particle size range of the granular filler is preferably an equivalent diameter ≤10μm; further preferably, the microscopic shape of the aluminum powder is lamellar.
[0017] For coatings that have not been sintered and modified, the above-mentioned filler powder can improve the performance of the coating and reduce the possibility of cracks in the coating during preparation and service. Among them, the single powders of aluminum, zinc, magnesium, and titanium can also be used as sacrificial materials during service, react preferentially, thereby filling the cracks that have already appeared in the coating and protecting the substrate, further improving the protective performance of the coating; for coatings that have been sintered and modified, the above-mentioned filler powder can compensate for the volume of the above-mentioned ceramic precursor shrinking during sintering, thereby avoiding cracks in the coating. Among them, the single powders of aluminum, zinc, magnesium, and titanium and some compound powders can also react with the ceramic precursor to generate a special mixed crystal structure containing amorphous and fine crystals, thereby further improving the performance of the coating. The single powders of aluminum, zinc, magnesium, and titanium can also react with the atmosphere to generate special compounds to improve the performance of the coating. The single powders of aluminum, zinc, and magnesium can even fill the cracks in the coating by melting themselves. In order to ensure that the coating has good performance under different service conditions and can coordinate deformation with different substrates to avoid cracks, the coating must contain at least one of the above fillers.
[0018] The coating raw materials are mixed to prepare the coating slurry. The filler can be in the form of powder or filler slurry formed by mixing the filler and the auxiliary solvent. After the filler and the auxiliary solvent are mixed into the slurry, the filler is wrapped by the auxiliary solvent. The auxiliary solvent can form a protective film on the surface of the filler, effectively avoiding the denaturation of the filler powder, and greatly improving the bonding between the filler powders and the wettability with different solutions. Preferably, when the filler is added to the coating slurry, the filler is in the form of slurry. Furthermore, the amount of the auxiliary solvent used in the slurry should be included in the total amount of the auxiliary solvent in the raw materials.
[0019] Among the raw material components of the coating, the auxiliary solvent is selected from one or more of hydrocarbons (such as isoalkanes, xylene, petroleum spirits), ethers (such as aromatic ethers, methyl ethers), alcohols (such as ethanol, methanol), esters (such as butyl acetate, ethyl acetate, methyl acetate), and silane coupling agents; when mixing the coating slurry, the auxiliary solvent can adjust the viscosity of the solution and improve the wettability of the coating, so that the coating slurry can be more easily attached to various substrate surfaces, thereby adapting to complex working conditions.
[0020] Among the raw material components of the coating, the auxiliary curing agent is selected from one or more of diazabicyclo, aluminum triacetylacetonate, and phosphazene; in the raw materials of the coating, the auxiliary curing agent mainly plays the role of adjusting the curing time of the coating slurry, improving the interface bonding between the metal and the coating, and enhancing the adhesion of the coating on the substrate. When the mass content of the auxiliary curing agent is greater than 20%, increasing the content of the auxiliary curing agent has no effect on shortening the curing time of the coating slurry. Therefore, according to the time and adhesion requirements of the curing process, the mass content of the auxiliary curing agent in the slurry ranges from 0 to 20%.
[0021] The present invention also proposes a method for preparing the composite protective coating for metal surface, comprising the following steps:
[0022] S1. Preparation of coating slurry: The coating raw materials are mixed in a certain proportion and uniformly without lumps to obtain a coating slurry;
[0023] S2 coating: the coating slurry prepared in S1 is evenly coated on the surface of the metal substrate to be protected to form a coating; the coating coating method may be roller coating, dip coating or spraying;
[0024] S3. Curing: Curing the coating prepared in S2 at a temperature range of 20-300°C to convert the coating slurry into a solid state; after curing, the auxiliary materials in the coating slurry evaporate or disappear after reacting with other raw materials, and the silicon-based ceramic precursor in the main material is converted into a pre-ceramic phase with a three-dimensional network distribution, and the filler exists in the gaps therein, forming a composite protective coating with a three-dimensional network-gap structure;
[0025] S4. Re-coating and curing: This step is performed selectively. When the coating thickness obtained after S3 is completed cannot reach the required coating thickness, S2 and S3 steps can be repeated multiple times until the required coating thickness is obtained.
[0026] Furthermore, the curing time of S3 should be determined in combination with the coating slurry ratio, curing temperature, and coating thickness factors: when there is no auxiliary curing agent, the coating is cured in the temperature range of 20~150℃, the curing time takes 4~120h, and when it is cured in the temperature range of 150~300℃, the curing time takes 30~240min; when an auxiliary curing agent is added, the coating is cured in the temperature range of 20~150℃, the curing time is shortened to 1~24h, and when it is cured in the temperature range of 150~300℃, the curing time takes 0.3~50min; when the coating thickness is greater than 70μm, the curing time should be appropriately extended as the coating thickness increases.
[0027] Further, when different methods are used for coating, the steps are as follows:
[0028] a) Roller coating: coating the coating slurry on the surface of the metal substrate using a rotating roller as a carrier, and removing the excess coating slurry on at least one surface of the substrate by air knife blowing or other methods before deposition and delamination, so as to control the thickness of the coating slurry on at least one surface;
[0029] b) Dip coating: immersing the metal substrate into a coating slurry pool for dip coating, and after the substrate leaves the coating slurry pool and before the coating slurry on at least one surface of the substrate is deposited and layered, removing excess coating slurry on the at least one surface by air knife blowing or centrifugation, so as to control the coating slurry thickness on at least one surface;
[0030] c) Spraying: The coating slurry is atomized and then sprayed on the surface of the substrate. Before the coating slurry on at least one surface of the substrate is deposited and layered, the thickness of the coating slurry on the at least one surface is controlled by adjusting the process parameters such as the nozzle spraying amount and the moving speed of the workpiece during spraying.
[0031] The coating has excellent anti-oxidation and anti-corrosion properties.
[0032] Furthermore, the coating can be modified by sintering to further improve the coating performance, and the process steps are: S5. Sintering: After completing S3 or S4, the coating and the substrate are kept at 300-1100°C for 0.5-30 minutes. After the coating is sintered and modified, part or all of the structure (preceramic phase and filler phase) of the coating is transformed, and at least one of the reaction of the preceramic phase, the reaction of the preceramic phase and the filler phase, and the reaction of the filler phase occurs, generating a ceramic structure with a polycrystalline state; the hardness of the coating will be significantly improved, which will be beneficial for the coating to serve in a more complex environment.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] 1. The coating slurry of the present invention has simple configuration, flexible composition control, and is easy to adapt to different production processes and production rhythms;
[0035] 2. The coating slurry coating process of the present invention is simple and can be prepared by various methods, such as roller coating, dip coating, spray coating, etc., which is conducive to adapting to different working conditions;
[0036] 3. The coating of the present invention has excellent anti-oxidation performance: by using the ceramic precursor of the above composition and adding fillers, a coating that is not easy to crack is prepared and the anti-oxidation performance of the coating is enhanced. When the coating is oxidized at 300-1100°C, the coating structure changes (the same reaction as sintering in oxygen). In this process, the filler phase can coordinate the deformation caused by the shrinkage of the ceramic precursor, reduce cracks, and avoid exposure of the substrate. At the same time, the pre-ceramic phase and the filler phase will also change, further enhancing the ability of the coating to protect the substrate;
[0037] 4. The present invention can selectively perform a sintering process on the coating in combination with the specific service environment, and modify and strengthen the coating, which is conducive to reasonable control of production costs. Under normal circumstances, the prepared coating can meet the substrate protection below 1100°C, and the coating does not need to be sintered; when there are special requirements for the coating performance (such as: high surface hardness, high dimensional accuracy), the coating needs to be sintered under conditions higher than the service temperature under the premise of selecting suitable fillers. The sintered coating has a stable structure and excellent anti-oxidation performance in high temperature and long-term (≥1h) service;
[0038] 5. The energy consumption cost of the coating production process of the present invention is lower than that of similar products. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 is a coating structure diagram of the present invention, Figure 1 (a) is a schematic diagram of the coating structure of the present invention, Figure 1 (b) is a SEM morphology image of the coating of Example 1 of the present invention;
[0041] Figure 2 The present invention is a flow chart of the method for preparing the composite protective coating for metal surface;
[0042] Figure 3 This is a surface macroscopic morphology of the cured coating in Example 1;
[0043] Figure 4 This is the morphology of the coating after sintering. Figure 4 (a) is a cross-sectional morphology of the coating after sintering at 400° C. in Example 1. Figure 4 (b) is a cross-sectional morphology of the coating in Example 1 after sintering at 950°C. DETAILED DESCRIPTION
[0044] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0045] Example 1
[0046] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0047] S1. Prepare coating slurry:
[0048] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0049] In the coating slurry, the mass ratio of each component is: main material is 80%, auxiliary solvent is 20%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. In the main material, the mass ratio of silicon-based ceramic precursor to filler is 4:1.
[0050] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0051] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0052] The auxiliary solvents and contents used in the coating slurry are: 50% dimethyl carbinol, 40% light aromatic hydrocarbons, and 10% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0053] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0054] S2. Coating:
[0055] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0056] S3. Curing:
[0057] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0058] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0059] Figure 1 is a coating structure diagram of the present invention, wherein Figure 1 (a) is a schematic diagram of the coating structure of the present invention, Figure 1 (b) is a SEM morphology of the coating of Example 1 of the present invention. It can be seen from the figure that the composite protective coating presents a three-dimensional network-gap structure, wherein the pre-ceramic phase is connected into a three-dimensional network structure in the coating, and its volume fraction is in the range of 20-80%, and the filler phase is distributed in the gap of the pre-ceramic phase, and its volume fraction is in the range of 20-80%.
[0060] Figure 2 The present invention is a flow chart of the preparation method of the composite protective coating for metal surface, wherein S1 to S4 are the preparation process steps of the coating, and S5 is the selective coating modification and enhancement process step.
[0061] Figure 3 This is a macroscopic morphology of the surface of the cured coating in Example 1. It can be seen from the figure that the coating uniformly wraps the metal substrate, the surface is dense and has no pore defects.
[0062] Figure 4 This is a cross-sectional morphology diagram of the coating after sintering in Example 1. Figure 4 The coating in (a) is sintered at 400°C, corresponding to the modified 1# in the example, wherein the filler part is slightly oxidized, but still corresponds to the filler phase of the original coating, and a smaller part of the ceramic precursor begins to undergo a ceramic transformation to generate a polycrystalline ceramic structure; Figure 4 The coating in (b) is sintered at 950°C, corresponding to the modified 3# in the example, in which a small part of the filler is oxidized to form filler phase oxide, which still belongs to the filler phase. Most of the filler reacts with the precursor of the ceramic transformation, and its product and the ceramic precursor product undergoing the ceramic transformation together form a polycrystalline ceramic phase.
[0063] Example 2
[0064] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, S3 curing, S4 re-coating and curing. Each step will be described in detail below.
[0065] S1. Prepare coating slurry:
[0066] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0067] In the coating slurry, the mass ratio of each component is: main material is 95%, auxiliary solvent is 5%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 8:1.
[0068] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥90%, and the rest is polysiloxane, and the sum of the mass fractions of the above components is 100%.
[0069] In the filler, the mass fraction of aluminum powder is ≥90%, and the rest is zinc powder, and the sum of the mass fractions of the above components is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0070] The auxiliary solvents and contents used in the coating slurry are: 10% light aromatics, 70% petroleum spirit, 5% ethanol, and 15% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0071] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0072] S2. Coating:
[0073] Use the spraying process to evenly apply the coating slurry on the clean substrate surface.
[0074] S3. Curing:
[0075] The sample was placed in a dry environment at 200°C for 2 hours. At the end of the time, the coating was completely cured.
[0076] S4. Re-spraying and curing
[0077] Use the spraying process to evenly apply the coating slurry on the cured coating surface again. Place the sample in a dry environment at 200°C for 1 hour. At the end of the time, the coating has been completely cured.
[0078] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0079] Example 3
[0080] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0081] S1. Prepare coating slurry:
[0082] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0083] In the coating slurry, the mass ratio of each component is: main material is 40%, auxiliary solvent is 60%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 1:1.
[0084] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥85%, and the rest is polysilocarbonane, and the sum of the mass fractions of the above components is 100%.
[0085] In the filler, the mass fraction of aluminum powder is ≥70%, and the rest is aluminum oxide and titanium oxide powder, and the sum of the mass fractions of the above components is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0086] The auxiliary solvents and contents used in the coating slurry are: 50% butyl acetate, 20% ethanol, and 30% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0087] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0088] S2. Coating:
[0089] Use the dipping process to evenly apply the coating slurry on the clean substrate surface.
[0090] S3. Curing:
[0091] The sample was placed in a dry environment at 150°C for 4 hours. At the end of the time, the coating was completely cured.
[0092] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0093] Example 4
[0094] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0095] S1. Prepare coating slurry:
[0096] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0097] In the coating slurry, the mass ratio of each component is: main material is 80%, auxiliary solvent is 20%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 4:1.
[0098] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥80%, and the rest is polysiloxane and polysilocarbazine, and the sum of the mass fractions of the above components is 100%.
[0099] In the filler, the mass fraction of aluminum powder is ≥80%, and the rest is silicon carbide and aluminum nitride powder, and the sum of the mass fractions of the above components is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0100] The auxiliary solvents and contents used in the coating slurry are: 70% petroleum spirit, 10% ethanol, and 20% dimethyl carbinol, and the sum of the mass fractions of the above components is 100%.
[0101] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0102] S2. Coating:
[0103] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0104] S3. Curing:
[0105] The sample was placed in a dry environment at 180°C for 1.8 hours. At the end of the time, the coating was completely cured.
[0106] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0107] Example 5
[0108] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0109] S1. Prepare coating slurry:
[0110] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0111] In the coating slurry, the mass ratio of each component is: main material is 70%, auxiliary solvent is 20%, auxiliary curing agent is 10%, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 6:1.
[0112] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥95%, and the rest is polysiloxane, and the sum of the mass fractions of the above components is 100%.
[0113] In the filler, the mass fraction of aluminum powder is ≥70%, and the rest is titanium and alumina powder, and the sum of the mass fractions of the above components is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0114] The auxiliary solvents and contents used in the coating slurry are: 90% petroleum spirit, 10% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0115] The auxiliary curing agent used in the coating slurry is: diazabicyclic.
[0116] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0117] S2. Coating:
[0118] Use the dipping process to evenly apply the coating slurry on the clean substrate surface.
[0119] S3. Curing:
[0120] The sample was placed in a dry environment at 100°C for 4 hours. At the end of the time, the coating was completely cured.
[0121] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0122] Example 6
[0123] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0124] S1. Prepare coating slurry:
[0125] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0126] In the coating slurry, the mass ratio of each component is: main material is 65%, auxiliary solvent is 15%, auxiliary curing agent is 20%, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 10:1.
[0127] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0128] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0129] The auxiliary solvent used in the coating slurry contains: 90% petroleum spirit, 10% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0130] The auxiliary curing agent used in the coating slurry is: aluminum triacetylacetonate.
[0131] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0132] S2. Coating:
[0133] Use the spraying process to evenly apply the coating slurry on the clean substrate surface.
[0134] S3. Curing:
[0135] The sample was placed in a dry environment at 150°C for 0.8h. At the end of the time, the coating was completely cured.
[0136] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0137] Example 7
[0138] In this embodiment, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, which comprises the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing. Each step will be described in detail below.
[0139] S1. Prepare coating slurry:
[0140] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0141] In the coating slurry, the mass ratio of each component is: main material is 60%, auxiliary solvent is 40%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 2:1.
[0142] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥70%, and the rest is polysilane and polysiloxane, and the sum of the mass fractions of the above components is 100%.
[0143] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0144] The auxiliary solvents and contents used in the coating slurry are: 60% petroleum spirit, 20% butyl acetate, and 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0145] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0146] S2. Coating:
[0147] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0148] S3. Curing:
[0149] The sample was placed in a dry environment at 120°C for 20 hours. At the end of the time, the coating was completely cured.
[0150] So far, a composite protective coating for metal surface according to the present invention has been prepared.
[0151] In order to more fully demonstrate the aluminum-containing protective coating for metal surface and the preparation method thereof according to the present invention, comparative examples 1 to 8 are provided.
[0152] Comparative Example 1
[0153] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0154] S1. Prepare coating slurry:
[0155] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0156] In the coating slurry, the mass ratio of each component is: the main material is 100%, the auxiliary solvent is 0, the auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of the silicon-based ceramic precursor to the filler is 100:1.
[0157] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0158] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0159] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0160] S2. Coating:
[0161] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0162] S3. Curing:
[0163] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0164] Comparative Example 2
[0165] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0166] S1. Prepare coating slurry:
[0167] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0168] In the coating slurry, the mass ratio of each component is: main material is 95%, auxiliary solvent is 5%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 13:1.
[0169] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0170] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0171] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0172] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0173] S2. Coating:
[0174] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0175] S3. Curing:
[0176] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0177] Comparative Example 3
[0178] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0179] S1. Prepare coating slurry:
[0180] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0181] In the coating slurry, the mass ratio of each component is: main material is 75%, auxiliary solvent is 5%, auxiliary curing agent is 20%, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 1:2.
[0182] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥90%, and the rest is polysilane and polycarbosilane, and the sum of the mass fractions of the above components is 100%.
[0183] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0184] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0185] The auxiliary curing agent and content used in the coating slurry are: 60% diazabicyclo and 40% aluminum triacetyl acetonate.
[0186] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0187] S2. Coating:
[0188] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0189] S3. Curing:
[0190] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0191] Comparative Example 4
[0192] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0193] S1. Prepare coating slurry:
[0194] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0195] In the coating slurry, the mass ratio of each component is: main material is 70%, auxiliary solvent is 30%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 3:1.
[0196] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0197] In the filler, the mass fraction of aluminum powder is ≤65%, and the rest is alumina powder, and the sum of the mass fractions of the above components is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0198] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0199] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0200] S2. Coating:
[0201] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0202] S3. Curing:
[0203] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0204] Comparative Example 5
[0205] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0206] S1. Prepare coating slurry:
[0207] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0208] In the coating slurry, the mass ratio of each component is: 35% of the main material, 65% of the auxiliary solvent, 0% of the auxiliary curing agent, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of the silicon-based ceramic precursor to the filler is 6:1.
[0209] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥80%, and the rest is polysilocarbonane, and the sum of the mass fractions of the above components is 100%.
[0210] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0211] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0212] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0213] S2. Coating:
[0214] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0215] S3. Curing:
[0216] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0217] Comparative Example 6
[0218] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the following steps: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0219] S1. Prepare coating slurry:
[0220] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0221] In the coating slurry, the mass ratio of each component is: main material is 80%, auxiliary solvent is 20%, auxiliary curing agent is 0, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 7:1.
[0222] In the silicon-based ceramic precursor, the mass fraction of polysilazane is ≤65%, and the rest is polysiloxane, and the sum of the mass fractions of the above components is 100%.
[0223] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0224] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0225] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0226] S2. Coating:
[0227] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0228] S3. Curing:
[0229] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0230] Comparative Example 7
[0231] In this comparative example, a low carbon steel plate is used as a substrate. The present invention relates to a method for preparing a composite protective coating for a metal surface, comprising the steps of: S1 preparing a coating slurry, S2 coating, and S3 curing.
[0232] S1. Prepare coating slurry:
[0233] The coating slurry of this embodiment is prepared in a dry room temperature environment.
[0234] In the coating slurry, the mass ratio of each component is: main material is 65%, auxiliary solvent is 10%, auxiliary curing agent is 25%, and the sum of the mass fractions of the above components is 100%. Among them, the mass ratio of silicon-based ceramic precursor to filler is 3:1.
[0235] In the silicon-based ceramic precursor, the mass fraction of polysilazane is 100%.
[0236] The mass fraction of aluminum powder in the filler is 100%. Before adding the filler, in order to make the filler have better wettability in the coating slurry, a proper amount of auxiliary solvent is used to mix the filler to form a slurry, and then the filler slurry is mixed with other components of the coating slurry.
[0237] The auxiliary solvent and content used in the coating slurry are: 80% butyl acetate, 20% silane coupling agent, and the sum of the mass fractions of the above components is 100%.
[0238] The auxiliary curing agent used in the coating slurry includes: phosphazene.
[0239] The above ingredients are weighed according to the above mass percentages and added into the container. The above ingredients are mixed by mechanical stirring for 3 minutes. At this time, the state of the mixed solution is a suspension of solid-liquid phases, and each ingredient is evenly dispersed in the solution without any agglomeration, agglomeration, sedimentation or other uneven mixing phenomenon.
[0240] S2. Coating:
[0241] Use roller coating process to evenly apply the coating slurry on the clean substrate surface.
[0242] S3. Curing:
[0243] The sample was placed in a dry environment at 250°C for 1 hour. At the end of the time, the coating was completely cured.
[0244] Comparative Example 8
[0245] A mild steel plate not coated with the coating slurry was used as the substrate.
[0246] Table 1 lists the types and proportions of raw materials used in Examples 1 to 10 and Comparative Examples 1 to 8 and related parameters for coating preparation, so as to facilitate comparison of the differences in parameters between different Examples and Comparative Examples.
[0247] Table 1
[0248]
[0249] Appearance evaluation and adhesion evaluation were performed on Examples 1 to 7 and Comparative Examples 1 to 8, and organization observation, thickness measurement, phase ratio statistics, and hardness measurement were performed on Examples 1 to 7 and some comparative examples.
[0250] The coating samples were prepared for metallographic observation, and the coating cross section was observed using a scanning electron microscope. The coating cross section thickness was measured using Image-Pro Plus 6.0 software, and the proportion of the filler phase in the coating cross section was statistically analyzed.
[0251] The coating hardness is rated using the pencil scratch method in standard GB-T6739-2022. The rating uses a Mitsubishi (UNI) 1887 pencil with a hardness range of 8B to 10H. When the surface hardness of the sample exceeds the 10H pencil scratch hardness, it is indicated by “>10H”.
[0252] The coating appearance is evaluated by visual inspection. In a clean environment with sufficient light, the surface quality of the coating is observed with the naked eye, especially whether the coating is flat, whether the thickness is uniform, whether the coating is damaged or cracked, and whether there are defects such as pits and peeling.
[0253] For the embodiments and comparative examples without obvious defects in appearance, the coating adhesion was evaluated. The grid method in standard GB / T9286-2021 was used as the evaluation method to visually inspect the coating shedding. The adhesion of 0 to 5 levels decreased in this order, with 0 being the best and 5 being the worst.
[0254] Table 2 lists the relevant data of appearance evaluation, adhesion evaluation, thickness, phase ratio and hardness in Examples 1 to 10 and Comparative Examples 1 to 8.
[0255] Table 2
[0256]
[0257] The samples with good coating appearance in Examples 1 to 7 and the comparative example were subjected to an oxidation resistance test and a corrosion resistance test.
[0258] Anti-oxidation performance test: The sample was oxidized in an air environment at 950°C for 60 minutes, and the Fe oxide content on the sample surface was tested using an X-ray diffractometer (XRD). The Fe oxide content obtained by XRD analysis was used as the standard to evaluate the oxidation degree of the coating. Among them, Fe oxide content ≥50% is severe oxidation; 50%>Fe oxide content ≥20% is relatively severe oxidation; 20%>Fe oxide content ≥5% is slight oxidation; 5%>Fe oxide content is no oxidation.
[0259] Corrosion resistance test: The corrosion resistance test of the coating was carried out in accordance with the test standards of GB / T 31588.1-2015 and GB / T 10125-2021. According to the requirements of the national standard, a NaCl neutral corrosion test solution was prepared, and the sample was subjected to a neutral salt spray test (NSS) under the cycle conditions of cycle B for 168 hours. After the experiment, the sample was taken out for surface observation. The product of salt spray corrosion usually refers to reddish-brown iron oxide. The corrosion resistance was evaluated by the area occupied by the corrosion product on the surface of the sample: if the corrosion product area is ≥50%, the corrosion resistance is extremely poor; if the corrosion product area is 50%> ≥20%, the corrosion resistance is poor; if the corrosion product area is 20%> ≥5%, the corrosion resistance is good; if the corrosion product area is 5%>, the corrosion resistance is excellent.
[0260] Table 3 lists the experimental results of the anti-oxidation performance test and the anti-corrosion performance test of the samples. The experimental results show that the coating has the ability to protect the substrate from oxidation for 60 minutes in an air environment at 950°C and also has good anti-corrosion performance.
[0261] Table 3
[0262]
[0263] The above-mentioned Examples 1 to 7 and Comparative Examples 1 to 8 illustrate that a composite protective coating with good performance can be prepared according to the coating slurry described in the present invention. In Comparative Examples 1 and 2, when there is too much ceramic precursor in the main material of the coating (too little filler phase), although a coating with good appearance and good corrosion resistance can be obtained, the organizational characteristics of the obtained coating are different from those of the coating described in the present invention. After oxidation in an air environment at 950°C for 60 minutes, the coating fails and does not have good oxidation resistance; in Comparative Example 3, when there is too little ceramic precursor in the main material of the coating (too much filler phase), the coating cannot be effectively cured, the filler cannot bond with the ceramic precursor, and the coating cannot be prepared; in Comparative Example 4, when the aluminum powder content in the filler is lower than the preferred content range of the present invention, the coating still has good corrosion resistance, but during the oxidation process in air at 950°C for 60 minutes, the coating fails to fully bond with the substrate. Coordinated deformation leads to decreased protection of the coating to the substrate and reduced antioxidant protection effect; in Comparative Example 5, too much auxiliary solvent is added and the concentration of the ceramic precursor is too low, making it difficult to form a continuous and uniformly thick cured coating. At the same time, a large amount of auxiliary solvent evaporates during the curing process, generating a large amount of gas, which increases the probability of coating defects and makes the coating incomplete; in Comparative Example 6, the polysilazane content in the ceramic precursor is lower than the above-mentioned preferred content. Although a coating with good appearance can still be formed after adding polysiloxane, its protective effect is obviously not as good as that of Examples 1 to 7; in Comparative Example 7, due to the excessive amount of auxiliary curing agent in the coating slurry, the coating slurry is overly viscous, and the gas in the slurry is difficult to escape during curing, resulting in coating defects and affecting the curing effect.
[0264] In order to highlight the characteristic that the coating of the present invention still has a certain coating protection ability after modification, the coating sample prepared in Example 1 is used as a sample and is modified by keeping it warm for 0 to 30 minutes in a temperature environment of 300 to 1100°C.
[0265] Modification of sample 1#: In an air atmosphere at 400°C, the sample was kept warm for 25 minutes for modification;
[0266] Modification of sample 2#: In an air atmosphere at 700°C, the sample was kept warm for 20 minutes for modification;
[0267] Modification of sample 3#: in an air atmosphere at 950℃, the sample was kept warm for 10 minutes for modification;
[0268] Modification of sample 4#: In an air atmosphere at 1000℃, the sample was kept warm for 3 minutes for modification;
[0269] Modification of sample 5#: In an air atmosphere at 1000℃, the sample was kept warm for 25 minutes for modification;
[0270] Modification of sample 6#: The sample was kept at 1050°C in a nitrogen atmosphere for 20 minutes for modification.
[0271] The modified coating was subjected to microstructure observation, thickness measurement, appearance observation and adhesion evaluation.
[0272] The coating samples were prepared for metallographic observation, and the coating cross section was observed using a scanning electron microscope. The coating cross section thickness was measured using Image-Pro Plus 6.0 software. The coating hardness was rated using the pencil scratch method.
[0273] The coating appearance is evaluated by visual inspection. In a clean environment with sufficient light, the surface quality of the coating is observed with the naked eye, especially whether the coating is flat, whether the thickness is uniform, whether the coating is damaged or cracked, and whether there are defects such as pits and peeling.
[0274] The coating hardness was rated for the coating sample using the pencil scratch method in standard GB-T6739-2022. The rating was performed using a Mitsubishi (UNI) 1887 model pencil with a hardness range of 8B to 10H. When the surface hardness of the sample exceeds the pencil scratch hardness of 10H, it is indicated by “>10H”. For the embodiments and comparative examples that did not show obvious defects in appearance, the coating adhesion was evaluated. The grid method in standard GB / T9286-2021 was used as an evaluation method to visually inspect the coating shedding, and the adhesion of 0 to 5 grades decreased accordingly, with 0 being the best and 5 being the worst.
[0275] The specific process parameters of the coating modification and the characteristics of the modified coating are shown in Table 4. From the observation results of the microstructure characteristics of the modified coating, it can be seen that a polycrystalline ceramic phase appears in the modified coating, and as the sintering temperature increases, the pre-ceramic phase in the coating gradually disappears. This part of the pre-ceramic phase is transformed into a polycrystalline ceramic phase, and the hardness of the coating is significantly improved. The surface cannot be damaged by the Mitsubishi (UNI) 1887 model 10H pencil with the highest hardness on the market.
[0276] Table 4
[0277]
[0278] The above-mentioned sintered modified 1#~6# coating samples were subjected to oxidation resistance test and corrosion resistance test.
[0279] Anti-oxidation performance test: The sample was oxidized in an air environment at 950°C for 60 minutes, and the Fe oxide content on the sample surface was tested using an X-ray diffractometer (XRD). The Fe oxide content obtained by XRD analysis was used as the standard to evaluate the oxidation degree of the coating. Among them, Fe oxide content ≥50% is severe oxidation; 50%>Fe oxide content ≥20% is relatively severe oxidation; 20%>Fe oxide content ≥5% is slight oxidation; 5%>Fe oxide content is no oxidation.
[0280] Corrosion resistance test: The corrosion resistance test of the coating was carried out in accordance with the test standards of GB / T 31588.1-2015 and GB / T 10125-2021. According to the requirements of the national standard, a NaCl neutral corrosion test solution was prepared, and the sample was subjected to a neutral salt spray test (NSS) under the cycle conditions of cycle B for 168 hours. After the experiment, the sample was taken out for surface observation. The product of salt spray corrosion usually refers to reddish-brown iron oxide. The corrosion resistance was evaluated by the area occupied by the corrosion product on the surface of the sample: if the corrosion product area is ≥50%, the corrosion resistance is extremely poor; if the corrosion product area is 50%> ≥20%, the corrosion resistance is poor; if the corrosion product area is 20%> ≥5%, the corrosion resistance is good; if the corrosion product area is 5%>, the corrosion resistance is excellent.
[0281] The experimental results of the anti-oxidation performance test and the anti-corrosion performance test of the samples are listed in Table 5. From the results, it can be seen that the modified coating still has the ability to protect the substrate from oxidation for 60 minutes in an air environment at 950°C, and also has good anti-corrosion performance.
[0282] Table 5
[0283]
[0284] In order to fully reflect the diversity of application scenarios of the composite protective coating of the present invention, examples 8 and 9 are used for illustration.
[0285] Example 8
[0286] The composite protective coating of the present invention is prepared on a clean aluminum alloy surface. In the coating slurry used, the main material accounts for 80% and the auxiliary material accounts for 20%; the ratio of ceramic precursor to filler in the main material is 4:1, and polysilazane is used as the silicon-based ceramic precursor; in the filler, aluminum powder accounts for 70%, and zinc-aluminum-magnesium alloy powder accounts for 30%. The coating is prepared by spraying, and the coating is kept warm for 2 hours in a 200°C environment. The coating is cured to complete the coating preparation. According to measurement and observation, the coating thickness is about 40μm, and the coating contains a pre-ceramic phase and a filler phase, the filler phase accounts for about 60%, and the coating has a good appearance. After the coating is prepared, the aluminum alloy is oxidized in an air environment at 600°C for 10 minutes, and no oxide generation is observed at the interface of the aluminum alloy substrate, indicating that the coating protects the aluminum alloy substrate from oxidation.
[0287] Example 9
[0288] The composite protective coating of the present invention is prepared on the surface of high-alloy heat-resistant steel. In the coating slurry used, the main material accounts for 80% and the auxiliary material accounts for 20%; the ratio of ceramic precursor to filler in the main material is 3:1, and polysilazane is used as the silicon-based ceramic precursor; in the filler, aluminum powder accounts for 80% and titanium oxide powder accounts for 20%. The coating is prepared by spraying, and the coating is kept warm for 2 hours in a 200°C environment. The coating is cured to complete the coating preparation. According to measurement and observation, the coating thickness is about 70μm, and the coating contains a pre-ceramic phase and a filler phase, the filler phase accounts for about 68%, and the coating has a good appearance. After the coating is prepared, the high-alloy heat-resistant steel is oxidized in an air environment at 1000°C for 30 minutes. No oxide generation is observed at the interface of the heat-resistant steel substrate, indicating that the coating protects the heat-resistant steel substrate from oxidation.
[0289] It should be noted that when common metal materials such as steel and aluminum are used, the substrate can be in the shape of plates, tubes, rods, profiles, etc., which will not affect the implementation effect of the aluminum-containing protective coating and its preparation method in the present invention.
[0290] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A composite protective coating for metal surface, characterized in that: The coating is composed of a preceramic phase formed by a silicon-based ceramic precursor and an aluminum-containing filler phase, the preceramic phase is connected to form a three-dimensional network structure in the coating, the filler phase is distributed in the gaps of the preceramic phase, and the coating presents a three-dimensional network-gap structure; The volume fraction of the pre-ceramic phase is ≤80%, and the volume fraction of the filler phase is ≥20%.
2. The coating according to claim 1, characterized in that The raw materials of the coating include main materials and auxiliary materials. The main material is composed of a silicon-based ceramic precursor and a filler, and the mass ratio of the ceramic precursor to the filler is 1:1 to 10:1; The auxiliary material is composed of an auxiliary solvent and an auxiliary curing agent, and the auxiliary material can be selectively added or not; the main material accounts for 40-100% of the coating slurry, the auxiliary solvent in the auxiliary material accounts for 0-60% of the coating slurry, and the auxiliary curing agent in the auxiliary material accounts for 0-20% of the coating slurry, and the sum of the mass percentages of the above components is 100%; Preferably, in the coating slurry, the main material accounts for 40-95% of the coating slurry, the auxiliary solvent in the auxiliary material accounts for 5-60% of the coating slurry, and the auxiliary curing agent in the auxiliary material accounts for 0-20% of the coating slurry, and the sum of the mass percentages of the above components is 100%.
3. The coating according to claim 2, characterized in that Among the raw material components of the coating, the silicon-based ceramic precursor is selected from at least one of polysilazane, polysiloxane, polycarbosilane, and polysilane; Preferably, in the silicon-based ceramic precursor, the mass fraction of polysilazane is ≥70%.
4. The coating according to claim 2, characterized in that Among the raw material components of the coating, the filler is composed of aluminum powder and other powders, and its composition by mass percentage is: aluminum powder 70-100%, other powders 0-30%, and the sum of the mass percentages of the above components is 100%; The aluminum powder in the filler is pure aluminum or aluminum alloy powder, and the aluminum alloy is preferably an alloy with an aluminum mass fraction of ≥90%; The other powders in the filler are selected from at least one of single powders of zinc, magnesium, titanium, and silicon, alloy powders of two or more elements of zinc, magnesium, titanium, and silicon, or compound powders containing aluminum, zinc, magnesium, titanium, and silicon.
5. The coating according to claim 4, characterized in that The other powders are selected from single powders of zinc, aluminum, magnesium, titanium, silicon or compound powders containing the above elements; the microscopic shape of the filler is one or both of lamellar and granular, the size range of the lamellar filler is preferably an equivalent diameter ≤70μm, and the particle size range of the granular filler is preferably an equivalent diameter ≤10μm.
6. The coating according to claim 2, characterized in that Among the raw material components of the coating, the auxiliary solvent component is selected from: one or more of hydrocarbons, ethers, alcohols, esters, and silane coupling agents; The auxiliary curing agent is selected from one or more of diazabicyclo, aluminum triacetylacetonate, and phosphazene.
7. The method for preparing a composite protective coating for a metal surface according to any one of claims 1 to 6, characterized in that: The steps include: S1. Preparation of coating slurry: The coating raw materials are mixed in a certain proportion and uniformly without lumps to obtain a coating slurry; S2 coating: the coating slurry prepared in S1 is evenly coated on the surface of the metal substrate to be protected to form a coating; S3. Curing: Curing the coating prepared in S2 at a temperature range of 20 to 300° C. to convert the coating slurry into a solid state; S4. Re-coating and curing: If the coating thickness after S3 is completed cannot reach the required coating thickness, S2 and S3 steps can be repeated multiple times until the required coating thickness is obtained.
8. The method according to claim 7, characterized in that In S2, the coating is applied by roller coating, dipping or spraying.
9. The method according to claim 7, characterized in that: In S3, when there is no auxiliary curing agent, the curing time is 4 to 120 hours when the coating is cured in the temperature range of 20 to 150°C, and the curing time is 30 to 240 minutes when it is cured in the temperature range of 150 to 300°C; when an auxiliary curing agent is added, the curing time is 1 to 24 hours when the coating is cured in the temperature range of 20 to 150°C, and the curing time is 0.3 to 50 minutes when it is cured in the temperature range of 150 to 300°C; when the coating thickness is greater than 70μm, the curing time should be appropriately extended as the coating thickness increases.
10. The method according to claim 7, characterized in that After the coating is prepared, sintering modification is performed, and the sintering modification step is: S5. Sintering: After S3 or S4 is completed, the coating and the substrate are kept warm in an environment of 300-1100° C. for 0.5-30 minutes.
Citation Information
Patent Citations
Method for producing a component from a steel product provided with an al-si coating and intermediate product of such a method
CN101932747A
A high-temperature resistant and environmentally friendly Dacromet coating, coating material and its preparation method
CN106700701B
High-toughness hot stamping aluminum-silicon coated steel plate and preparing method thereof
CN110484820A
A chromium-free Dacromet coating solution, its preparation method and application
CN114456711B
A high-hardness, chromium-free Dacromet coating, an anti-corrosion coating, and its preparation method
CN115433483B